PERSISTENT BREAST PAIN FOLLOWING BREAST CANCER SURGERY IS ASSOCIATED WITH PERSISTENT SENSORY CHANGES, PAIN INTERFERENCE, AND FUNCTIONAL IMPAIRMENTS - Langford, Dale J. (J Pain, 2014)
Inter-individual variability exists in persistent breast pain following breast cancer surgery. Recently, we used growth mixture modeling to identify three subgroups of women (n=398) with distinct persistent breast pain trajectories over six months following surgery (i.e., Mild, Moderate, Severe). Purposes of this study were to identify demographic and clinical characteristics that differed among the breast pain classes and, using linear mixed effects modeling, determine how changes over time, in sensitivity in the breast scar area, pain qualities, pain interference, and hand and arm function differed among these classes. Several demographic and clinical characteristics differentiated the breast pain classes. Of note, 60% to 80% of breast scar sites tested were much less sensitive than the unaffected breast. Significant group effects were observed for pain qualities and interference scores, such that, on average, women in the Severe Pain class reported higher scores than women in the Moderate Pain class. In addition, women in the Moderate Pain class reported higher scores than women in the Mild Pain class. Compared to the Mild Pain class, women in the Severe Pain class had significantly impaired grip strength and women in the Moderate and Severe Pain classes had impaired flexion and abduction.